Navigating the investment minefield : a practical guide to avoiding mistakes, biases, and traps - Baker, H. Kent; Puttonen, Vesa (Emerald Publishing Limited, 2019)
When you think about investing, what words come to mind? Overwhelming? Intimidating? Scary?Investors face a vast array of investment options vying for their business. They are aware that some of those providing these "opportunities" seek to take advantage of them. And although most investors realize they are fallible, they often have no clear idea why or what they can do about it. So what chance do less savvy investors have navigating the investment minefield and emerging unscathed?The answer is not much-unless they recognize the pitfalls along the way. In this book, H. Kent Baker and Vesa Puttonen show new investors how to avoid rash financial decisions and basic investing sins. They help them to recognize and avoid common investing mistakes, behavioral biases, and traps that can affect sound judgment and reduce wealth. Ultimately, they explain how to separate investment fads from time-tested investment principles-a task that is easier said than done, but that is well worth the effort.Navigating the Investment Minefield is essential reading for novice investors, and it is of keen interest to more seasoned investors seeking a refresher course on the most basic, time-honored truths of wealth management.